Survival rate of different fixed posterior space maintainers used in Paediatric Dentistry - A systematic review - Mahesh Ramakrishnan; R. Dhanalakshmi; E.M.G. Subramanian (Elsevier, 2019)
Purpose: Space Maintainers have long been used for the management of space loss in primary and mixed dentition, but there is a need to have an evidence based approach when selecting the most appropriate space maintainer for space management in children. This systematic review aimed to assess the survival rate of space maintainers in children. Methods: A systematic literature search was conducted until October 2017 using PubMed, Scopus, and The Cochrane Central Register of Controlled Trials databases to identify peer- reviewed papers published in English. Search keywords and MeSH headings include "primary dentition" and "Fixed Space maintainers". The inclusion criteria were clinical studies conducted in children less than 12 years of age, who required unilateral or bilateral fixed space maintainer. Retrieved papers were evaluated by four reviewers independently to assess suitability for inclusion in the systematic review and the final decision was made by consensus. Qualities of the included studies were assessed using Quality of Reporting of Observational Longitudinal Research by Oxford Academics and data were extracted for analysis. Results: The search identified a total of 39 papers for screening after removal of duplicate articles. Among the retrieved studies, 23 papers did not satisfy the study inclusion criteria. Consequently, 16 full text articles were retrieved and reviewed. Finally, those 11 papers which fulfilled all the inclusion criteria were selected and reviewed systematically. Most of the clinical trials were assessed as having moderate and low risk of bias. Conclusion: There is a wide variation in the survival rate of metal based and resin based space maintainers and also within the metal based space maintainers. There is an inadequate evidence to recommend one best fixed space maintainer due to lack of properly designed studies. Hence, clinical trial comparing different types of metal based space maintainer and resin based space maintainer with longer duration of follow-up must be performed to evaluate its survival rate. Keywords: Survival rate, Longevity, Fixed space Maintainer, Band and loop